ANALISIS PENGARUH INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING PADA PRODUK GULA PASIR SEBELAS (GUPALAS) PABRIK GULA SEMBORO PTP NUSANTARA XI (PERSERO) - Putu Sukarmen; R. Andi Sularso; Deasy Wulandri (Jurnal Ekonomi Akuntansi dan Manajemen, 2015)
This study aimed to examine the effect of product innovation on consumer satisfaction with a competitive advantage as an intervening variable in sugar products (Gupalas) at Sugar Factory Semboro PTP Nusantara XI (Persero). In this study there are three hypotheses, namely product innovation affect customer satisfaction, product innovation affect the competitive advantage and competitive advantage effect on customer satisfaction. Consumer research population is the end gupalas in Jember. By using a sampling technique Purpusive Sampling, obtained 173 respondents was conducted in January and February 2013.